Adaptation to Portuguese of the Depression, Anxiety and Stress Scales (DASS) Adaptación para la lengua portuguesa de la Depression, Anxiety and Stress Scale (DASS) Adaptação para a língua portuguesa da Depression, Anxiety and Stress Scale (DASS) - João Luís Alves Apóstolo; Aida Cruz Mendes; Zaida Aguiar Azeredo (Universidade de São Paulo, 2006)
Objective: to adapt to Portuguese, of Portugal, the Depression, Anxiety and Stress Scales, a 21-item short scale (DASS 21), designed to measure depression, anxiety and stress. Method: After translation and back-translation with the help of experts, the DASS 21 was administered to patients in external psychiatry consults (N=101), and its internal consistency, construct validity and concurrent validity were measured. Results: The DASS 21 properties certify its quality to measure emotional states. The instrument reveals good internal consistency. Factorial analysis shows that the two-factor structure is more adequate. The first factor groups most of the items that theoretically assess anxiety and stress, and the second groups most of the items that assess depression, explaining, on the whole, 58.54% of total variance. The strong positive correlation between the DASS 21 and the Hospital Anxiety and Depression scale (HAD) confirms the hypothesis regarding the criterion validity, however, revealing fragilities as to the divergence between theoretically different constructs. Objetivo: adaptar a la lengua portuguesa, de Portugal, la Depression, Anxiety and Stress Scale, versión corta de 21 ítems, (DASS-21), que permite evaluar depresión, ansiedad y estrés. Método: Después de haber sido traducida y retrovertida, con la ayuda de peritos, la DASS-21 fue administrada a enfermos en consulta externa de psiquiatría (N=101), y fue evaluada la consistencia interna, la validez de constructo y la validez concurrente. Resultados: Las propiedades de la DASS-21 atestiguan su calidad para evaluar estados emocionales. El instrumento reveló buena consistencia interna. El análisis factorial muestra que la estructura de dos factores es la más ajustada. El primer factor agrupa la mayoría de los ítems que teóricamente evalúan ansiedad y estrés, y el segundo agrupa la mayoría de los ítems que evalúan depresión, explicando en su conjunto el 58,54% de la variación total. La fuerte correlación positiva entre la DASS-21 y la escala Hospital Anxiety and Depression confirma la hipótesis relativa a la validez de criterio, siendo sin embargo reveladas fragilidades relativamente a la divergencia entre constructos teóricamente diferentes. Objetivo: adaptar para a língua Portuguesa, de Portugal, a Depression, Anxiety and Stress Scale, versão curta de 21 itens (DASS-21), que permite avaliar depressão, ansiedade e estresse. Método: Após ter sido traduzida e retrovertida, com a ajuda de peritos, a DASS-21 foi administrada a doentes em consulta externa de psiquiatria (N=101), e foi avaliada a consistência interna, a validade de construto e a validade concorrente. Resultados: As propriedades da DASS-21 atestam a sua qualidade para avaliar estados emocionais. O instrumento revelou boa consistência interna. A análise fatorial mostra que a estrutura de dois fatores é mais ajustada. O primeiro fator agrupa a maioria dos itens que teoricamente avaliam ansiedade e estresse e o segundo agrupa a maioria dos itens que avaliam depressão, explicando no seu conjunto 58,54% da variância total. A forte correlação positiva entre a DASS-21 e a HAD confirma a hipótese relativa à validade de critério, sendo no entanto reveladas fragilidades relativamente à divergência entre construtos teoricamente diferentes.